Efficient treatment of brine wastewater through a flow-through technology integrating desalination and photocatalysis. (15th June 2019) - Ye, Gui; Yu, Zhiyong; Li, Yiming; Li, Lei; Song, Li; Gu, Li; Cao, Xuebo
Abstract: Many current treatments for brine wastewaters are energy-intensive, chemical-intensive, and involve independent process in the removal of salts and contaminants. We demonstrate that through the integration of capacitive deionization and photocatalysis reactions within carbon nanotubes (CNTs) based membrane system, we are able to realize the purification and desalination of wastewaters via single-step, energy-efficient, and environmentally friendly route. We firstly designed the membrane system consisting of graphitic carbon nitride (g-C3 N4 ), CNTs membrane, and poly(vinyl alcohol)-formaldehyde (PVF) foam. Then, two identical membrane systems were used as permeable electrodes and photocatalytic microreactors to construct the flow-through setup. The tests of the setup with a variety of dye solution, antibiotics solution, and actual wastewaters prove that wastewaters passing through the setup promptly turn to clean water with significantly decreased salinity. This is because the setup can use C3 N4 modified CNTs membrane to adsorb organic contaminants and inorganic ions and decompose contaminants via photocatalysis reactions. In addition, by discharging the setup, its adsorption capacity towards salts is easily recovered. Consequently, the flow-through setup is observed to exhibit stable performance for concurrent removal of organic contaminants and inorganic salts in multiple cycles. Graphical abstract: Image 1 Highlights: A ternary membrane consisting of C3 N4 nanoparticles, self-assembled carbon nanotubes, and PVF foam was prepared. A flow-through setup using ternary membranes as the key component was fabricated. The flow-through setup integrates dual functionalities for capacitive deionization and photocatalysis. The flow-through setup demonstrates high efficiency in treating brine wastewaters.